2017
DOI: 10.3174/ajnr.a5359
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intracranial Aneurysms in Patients with Aortic Dissection

Abstract: Patients with aortic dissection have a high prevalence of intracranial aneurysms, and selective screening for brain vessels could be considered in these patients with arch vessel involvement. A further prospective study is needed to demonstrate a substantial prevalence of intracranial aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Three studies investigated the proportion of patients with aortic aneurysm or BAV in patients suffered from IA. [19][20][21] Ten studies reported a prevalence of IA in patients with aortopathy: two studies were in patients with BAV; 10,13 three studies considered patients with CoA; 9,11,12 three studies were conducted in patients with aortic aneurysm; 5,7,8 one study investigated aortic dissection; 3 and one study examined both aortic aneurysm and aortic dissection. 6 Seven studies were from the USA, and three studies from South Korea.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies investigated the proportion of patients with aortic aneurysm or BAV in patients suffered from IA. [19][20][21] Ten studies reported a prevalence of IA in patients with aortopathy: two studies were in patients with BAV; 10,13 three studies considered patients with CoA; 9,11,12 three studies were conducted in patients with aortic aneurysm; 5,7,8 one study investigated aortic dissection; 3 and one study examined both aortic aneurysm and aortic dissection. 6 Seven studies were from the USA, and three studies from South Korea.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seven risk factors ( Supplementary Figures 1-7) were reported in three or more studies: female gender, 3,6,7,9-13 smoking, 3,6,7,[10][11][12][13] hypertension, 3,6,7,10-13 age, 6,9,11,13 diabetes, 3,6,7,13 hyperlipidemia, 3,6,7 and the overlapping of two aortic diseases. 7,9,[11][12][13] Pooled analyses yielded effect estimates for the effect of risk factors on the increased prevalence of IAs ( Figure 3…”
Section: Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations